Chemerin located in bone marrow promotes osteogenic differentiation and bone formation via Akt/Gsk3β/β‐catenin axis in mice. Issue 8 (25th January 2021) - Li, Jun; Zhang, Ting; Huang, Chenglong; Xu, Min; Xie, Wenhua; Pei, Qilin; Xie, Xinxin; Wang, Bin; Li, Xi
Abstract: Chemerin, a secreted protein mainly produced by adipocytes and hepatocytes, plays a variety of roles in endocrine or paracrine signaling. As reported in human epidemiology, chemerin was correlated with osteoporosis. And the previous in vitro study found that chemerin knockdown promoted osteogenesis and inhibited adipogenesis. However, the function of chemerin in bone metabolism and the underlying mechanism remains unclear. In this study, we uncovered the in vivo function of chemerin in bone homeostasis. We discovered that in obese mice, chemerin was increased in serum, while decreased in the bone marrow; and the chemerin expression in bone tissue was positively correlated with osteogenic genes. To further investigate the function of chemerin in bone metabolism, we generated chemerin deficiency and overexpression mice. We found bone mass and osteogenesis were decreased in chemerin deficiency mice, while were increased in chemerin overexpression mice. Furthermore, we observed that the chemerin expression increased during osteogenic differentiation of MSCs. Besides, we verified that chemerin promoted osteogenic differentiation in C3H10T1/2 cells and BMSCs through Akt/Gsk3β/β‐catenin axis. Treatment with Akt inhibitor (MK2206) abolished the promoting effect of chemerin on osteogenic differentiation and active β‐catenin. Together, our results suggest chemerin in bone marrow, not in serum, promotes osteogenic differentiation and bone formation via Akt/Gsk3β/β‐catenin axis. Chemerin may serve as a therapeutic strategy for osteoporosis. Graphical abstract: We found that chemerin promotes osteogenic differentiation and bone formation via activating Akt/Gsk3β/β‐catenin axis, and this promoting effect attributes to the chemerin in bone marrow locally, not in the serum. Our findings provide new insight into the effects of chemerin on bone metabolism, and chemerin might be a new potential target for the prevention and treatment of osteoporosis.